Maturity levels of sustainable corporate entrepreneurship: The role of collaboration between a firm's corporate venture and corporate sustainability departments - Jeremy Schönwälder; Anja Weber (Business Strategy and the Environment, 2022)
To shed light on how incumbent firms implement sustainable corporate entrepreneurship (SCE) processes, this study investigates how organizations connect sustainability and venture departments. Based on qualitative interviews with 14 experts from 12 multinational corporations headquartered in Germany, we identified five maturity levels of SCE with increasing cross-functional collaboration: Non-Existent, Occasional, Expert, Collaboration, and Strategic Collaboration. Using secondary interview data from seven multinational companies headquartered outside Germany, we find initial support for these collaboration types in an international context. Results indicate that a company's general approach to innovation is associated with its SCE maturity level: companies with dedicated entrepreneurship units are more likely to have a higher level of SCE focus. Furthermore, the likelihood of working on radical innovations for sustainability seems to increase as soon as venture experts collaborate with sustainability managers, which, in turn, increases the chances of initiating sustainability transitions.
Keywords: 330; corporate sustainability; corporate venture; cross-functional collaboration; maturity model; sustainable corporate entrepreneurship